High Prevalence of Sequences Included in Transmission Clusters Within Newly Diagnosed HIV-1 Patients in Southern Spain (2004-2015) - González-Doménech, Carmen María; Sena Corrales, Gabriel; Viciana-Ramos, María Isabel; Palacios-Muñoz, María Rosario; Mora-Navas, Laura; Clavijo-Frutos, Encarnación; Santos-González, Jesús Leandro (Mary Ann Liebert, 2020)
The presence of transmission clusters (TCs) and their epidemiological characteristics in a treatment-naive cohort of HIV-1 patients in southern Spain over a decade (2004-2015) were evaluated. Protease and reverse transcriptase sequences provided by each genotype test were used in the phylogenetic study, performed first by the neighbor-joining method and then confirmed by Bayesian analysis. We collected clinical, immunovirological, and demographic data for all patients included. Our cohort comprised 757 patients, 428 (56.5%) belonging to a TC. Overall, we found 123 TCs, 21 of them comprising five or more individuals and three with ≥10 sequences. Forty-three TCs (35.0%) remained active. The clustered patients were mainly men (92.8%) who had sex with men (MSM) (81.5%), Spanish (80.6%), and young adults (median age at diagnosis of 32.6 years). They had lower percentages of late diagnosis and AIDS cases (42.1% and 13.6%, respectively), whereas the presence of recent seroconverters (31.1%), HIV-1 B subtypes (79.4%), and transmission drug resistance (20.3%) increased within TCs, with regard to not-clustered individuals. Among the TCs of non-B variants, circulating recombinant forms (CRF) were predominant (87.5%), with the highest frequencies for CRF19_cpx (17.0% of non-B subtype sequences in TCs); CRF02_AG (15.9%); and CRF01_AE (9.1%). In conclusion, over half of our cohort was included within a TC. More than a third of TCs found could be considered active transmission events. Belonging to a TC was related to MSM, Spanish origin, recent seroconversion, high prevalence of resistance mutations, and B HIV subtype. Among the non-B genetic forms in TCs, we found a high prevalence of CRF19_cpx, CRF02_AG, and CRF01_AE variants.
Keywords: Epidemiología molecular; HIV-1; Drug resistance mutations; Molecular epidemiology; Southern Spain; Transmission events